Organometallic small molecule kinase inhibitors – direct incorporation of Re and 99mTc into Opaganib®. Issue 98 (24th November 2021) - Lengacher, Raphael; Wang, Youchao; Braband, Henrik; Blacque, Olivier; Gasser, Gilles; Alberto, Roger
Abstract : Replacing an adamantyl unit in the protein kinase inhibitor Opaganib® with an integrated [(η 5 -Cp)M(CO)3 ] (M = Re, 99m Tc ) unit retains the lead's bioactivity and yields a true matched-pair pharmacomimetic. Abstract : [(η5-Cp)Re I (CO)3 ] was incorporated into the kinase inhibitor Opaganib®. The resulting bioorganometallic complex showed a similar anti-cancer activity to Opaganib® against PC-3 cancer cells. The IC50 value for the kinase SK2 is 30x higher than that of Opaganib®. The 99m Tc homologue was synthesized, completing a matched-pair for molecular theranostics.